2010
DOI: 10.1007/s11571-010-9143-8
|View full text |Cite
|
Sign up to set email alerts
|

Online learning and stimulus-driven responses of neurons in visual cortex

Abstract: In understanding how visual scene is processed in visual cortex, it has been an intriguing problem for theoretical and experimental neuroscientists to examine the relationship between visual stimuli and the induced responses of visual cortex. In particular, it is less explored whether and how the collective responses of visual neurons are patterned to reflect the geometrical regularities. In this paper, through a computation model and statistical analysis, we show that the orientation preference maps induced f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The concentric RFs of GCs and LGN cells are responsible for the primary integrations of physical stimuli, and all the subsequent visual tasks stem from the representation produced by these cells. It is found that the orientation preference maps caused by correlated visual stimuli show geometrical regularities similar to those observed in natural images (Tang et al 2011). Hubel and Wiesel, two Nobel Prize laureates, proposed a famous hypothesis about the construction of simple cells' RFs.…”
Section: Orientation Detection In the Brainmentioning
confidence: 83%
“…The concentric RFs of GCs and LGN cells are responsible for the primary integrations of physical stimuli, and all the subsequent visual tasks stem from the representation produced by these cells. It is found that the orientation preference maps caused by correlated visual stimuli show geometrical regularities similar to those observed in natural images (Tang et al 2011). Hubel and Wiesel, two Nobel Prize laureates, proposed a famous hypothesis about the construction of simple cells' RFs.…”
Section: Orientation Detection In the Brainmentioning
confidence: 83%